Sleep Quality and Sleepiness Among Veterinary Medical Students Over an Academic Year - Nappier, Michael T.; Bartl-Wilson, Lara; Shoop, Tiffany; Borowski, Shelby (Frontiers in Veterinary Science, 2019)
Good sleep health is a key component to good personal well-being. It has been postulated that veterinary students have poor sleep health, but few measurements have been undertaken. This study measured Pittsburgh Sleep Quality Index and Epworth Sleepiness Scale values at multiple points throughout an academic year for students in a veterinary medical curriculum. Students were found to have overall poor sleep quality and above average to excessive daytime sleepiness. Further investigation is necessary to determine specific causes as well as what action can be taken to improve student sleep health.